Causal Analysis and Resolution with Theory of Constraints: The CARTOC Method - Oliveira, Yure Ouriques; Cerdeiral, Cristina; Santos, Gleison (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Several problems can affect software development projects. Less complex problems can be solved punctually, or by applying simple Cause Analysis techniques which typically requires a low analysis effort. Problems of greater complexity, which occasionally affect other projects, are difficult to infer and require more extensive analysis effort possibly using more complex techniques. Also, not all factors that cause a complex problem have the same impact on the problem root cause. Knowing how to properly identify the problem root cause is critical to avoid its recurrence. We present the CARTOC method that structures the process of human reasoning to reduce the bias of those involved with the analysis during the root cause identification phase, validate established cause and effect relationships, and direct treatment of the identified causes. To achieve these objectives, CARTOC uses the Thinking Processes of the Theory of Constraints. We present a case study which produced evidences of CARTOC and Thinking Processes applicability to cause analysis and problem solving.